Does Mexico benefit from the Clean Development Mechanism? A model-based scenario general equilibrium analysis. (2nd June 2015) - Montaud, Jean-Marc; Pecastaing, Nicolas
Abstract: Since 2000, the Clean Development Mechanism (CDM) under the Kyoto Protocol has included southern countries in the fight against climate change by encouraging northern countries to make environmentally friendly direct investments at the lowest cost in these developing nations. Although CDM investments have enjoyed great success, the question of the contribution of these investments to the development of the host countries remains insufficiently explored. This paper offers a computable general equilibrium model-based scenario, describing the potential economic and environmental impacts of CDM investments for Mexico. As modelled in this study, these investments should generate both additional demand for activities that produce the fixed capital goods required for their implementation and environmentally friendly technological changes in the production process for the electricity sector. The numerical simulations reveal the growth potential and important fund of development represented by the CDM for Mexico; however, they show that the environmental impact also appears broadly mixed and dependent on both the nature of the sectors it affects and the intensity of the technological change it generates.